Amaranth proteins as a source of antioxidant peptides: Effect of proteolysis - Tironi, Valeria Anahi (2010)
The antioxidant activity of peptides present in the phosphate buffer-soluble fraction of: – Amaranthus mantegazzianus protein isolates (Is), – protein fractions (Albs, Globs, GlobPs and Gluts), alcalase hydrolysates of isolates (hydrolysis degree –HD-: 2.4% (IHls) and 30% (IHhs) and protein fractions (AlbHs, GlobHs, GlobPHs, and GlutHs) was investigated. Fractions separated by molecular exclusion chromatography were also analyzed. ABTS+. scavenging method showed the presence of antioxidant peptides in Is, Albs, Globs, and Gluts, being the last the one with the highest activity. No activity was detected in the GlobPs. After hydrolysis, the scavenging activity of all samples increased, especially at high HD. The GlobPs fraction presented the highest scavenging capacity after hydrolysis. Naturally-occurring peptides and polypeptides presented also the capacity to inhibit the linoleic acid oxidation, which was partially lost after hydrolysis. FPLC fractionation evidenced the appearance of <0.5 kDa active peptides due to the hydrolysis process. Results suggest the presence in the Is and IHhs of several peptides and polypeptides which can act as antioxidants by different mechanisms.